Tooth reattachment: knowledge and practice of Nigerian dentists in postgraduate training (2017)
Introduction. Trauma to teeth is relatively common and reattachment of fractured fragment is one of the available treatment modalities. It is conservative, provides immediate treatment with natural esthetics and faster restoration of function. Aim of the study. To assess the knowledge of resident doctors on tooth reattachment and investigate how much of this has been translated into current good clinical practice. Methodology. A cross-sectional study that made use of structured self-administered questionnaires completed by resident doctors from different dental specialties in Nigeria. The questionnaire included the demographics of respondents, knowledge about tooth reattachment, sources of information, practice of the procedure amongst others. Data was analysed with SPSS version 20, and p-value was set at ≤0.05. Result. Participants were aged between 28 and 57 years with mean of 35.1±5.7 years. The majority (95.7%) claimed they had heard about reattachment and 46.7% of these had more than one source of information. About 53% claimed it is indicated in tooth fracture while 4.3% of them stated that tooth avulsion is an indication. Also 53.2% believed that only anterior teeth could benefit from this procedure. Forty-two respondents had observed reattachment procedure before, out of which 18 (42.9%) had actually done it (p=0.04). A majority (89%), however, indicated a willingness to have a hands-on training workshop on the procedure. Conclusion. Though there is good awareness of reattachment, the practice is very low in this environment. There is, therefore, a need to create even more awareness on the current standard of practice of tooth reattachment among Nigerian dentists.